2014
DOI: 10.1039/c3cc49690b
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous assembly of iridium nanochain-like structures: surface enhanced Raman scattering activity using visible light

Abstract: A facile, environmentally friendly approach to synthesize branched Ir nanochain-like structures under mild conditions, using polyfunctional capping molecules in an aqueous medium is reported; the nanostructures exhibit a surface plasmon resonance peak (SPR) in the visible region and serve as an active substrate for surface enhanced Raman scattering studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 32 publications
0
14
0
Order By: Relevance
“…Iridium nanochain-like structures were prepared using sodium borohydride as a reducing agent and ascorbic acid (AA, which is biocompatible) as a capping agent in aqueous medium. 26 In a typical synthesis, an aqueous IrCl 3 solution (1 mM) was stirred in the presence of 2 mM ascorbic acid followed by the addition of freshly prepared sodium borohydride solution (20 mg in 10 mL water) and the mixture was heated at 80 1C in air under magnetic stirring for 6 hours and cooled down to room temperature. During the reaction, the colour of the solution changed from light pale yellow to light brown.…”
Section: Synthesis Of Ir Nanochainsmentioning
confidence: 99%
“…Iridium nanochain-like structures were prepared using sodium borohydride as a reducing agent and ascorbic acid (AA, which is biocompatible) as a capping agent in aqueous medium. 26 In a typical synthesis, an aqueous IrCl 3 solution (1 mM) was stirred in the presence of 2 mM ascorbic acid followed by the addition of freshly prepared sodium borohydride solution (20 mg in 10 mL water) and the mixture was heated at 80 1C in air under magnetic stirring for 6 hours and cooled down to room temperature. During the reaction, the colour of the solution changed from light pale yellow to light brown.…”
Section: Synthesis Of Ir Nanochainsmentioning
confidence: 99%
“…8,9 Their unique optical, electronic and magnetic properties are utilized for applications ranging from sensing, SERS, etc. [9][10][11] The synthesis protocol for one dimensional assemblies in the form of nanochains and structured nanoparticles has been developed for face centered cubic (FCC) metals like Ag, 12 Au, 13 Pd, 14 Ir, 15 Rh, 16 etc. but is less established for hexagonally close packed (HCP) metals.…”
mentioning
confidence: 99%
“…The chemical characteristics of Iridium nanoparticles is mainly based on composition, and surface morphology. It was identified that, the surface enhanced Raman scattering was studied well for Iridium nanochains than Iridium nanoparticles [23][24]. Nanomaterials based on transition metals and noble metals show versatile chemical properties.…”
Section: Recentlymentioning
confidence: 99%